INVESTIGATING THE INFLUENCE OF ION BOMBARDMENT AND SEQUENTIAL HEATING ON THE SURFACE COMPOSITION OF MONOCRYSTALLINE COPPER - Sodikjanov Jakhongirbek Shukhratbek ugli (European Science Publishing, 2024)
This study delves into the transformative effects of ion bombardment and subsequent thermal treatment on the surface composition of monocrystalline copper. Employing state-of-the-art surface analysis techniques such as X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS), our investigation aims to unravel the nuanced interplay between ion-induced alterations and thermal dynamics at the atomic level. Initial ion bombardment induces structural modifications and defect formation on the monocrystalline copper surface. Sequential heating, mimicking real-world conditions, serves as a catalyst for dynamic surface evolution, shedding light on the temporal changes in elemental distribution and chemical states. Through a meticulous exploration of these processes, we uncover insights into surface restructuring, oxidation kinetics, and the development of surface oxides. This research not only advances our fundamental understanding of the intricate relationship between ion bombardment and thermal influences on monocrystalline copper but also holds practical implications for fields such as semiconductor technology and materials engineering. The outcomes contribute to the refinement of surface engineering methodologies, guiding the design of materials with tailored surface properties for diverse applications.
Keywords: morphology, ion implantation, electronic structure, nanocrystalline, properties.